1949
DOI: 10.5935/0305-7518.19490002
|View full text |Cite
|
Sign up to set email alerts
|

Two-and-a-Half Years' Experimental Work on the Sulphone Group of Drugs

Abstract: This patient has had a history of l eprosy since I9I7 and illustrates the usual , experience in such cases of having been "'Bacteriologic index. To estimate the bacteriologic index add up the total numuer of positive smears and divide by sixteen. The bacteriologic index will thus vary from 6.uo to 0, the former being from a case where all smears are 6 plus and the latter from the case which shows no bacilli in any of the smears taken. (e.g. If the plus values of all the sixteen smears added up gives a total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

1950
1950
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…2 This was followed by other firstline drugs, such as clofazimine 3 in 1962 and rifampin 4 in 1970. Dapsone-resistant leprosy was first proved by Petit and Rees in 1964, 5 while resistance to rifampin 6 and to clofazimine 7 was subsequently reported.…”
Section: Introductionmentioning
confidence: 99%
“…2 This was followed by other firstline drugs, such as clofazimine 3 in 1962 and rifampin 4 in 1970. Dapsone-resistant leprosy was first proved by Petit and Rees in 1964, 5 while resistance to rifampin 6 and to clofazimine 7 was subsequently reported.…”
Section: Introductionmentioning
confidence: 99%
“…12 Injectable promin was replaced by a more effective oral sulfone, dapsone (4-4′-diaminodiphenyl sulfone, DDS), 6 years later. 13,14 Rifampicin, clofazimine, and minocycline were introduced subsequently.…”
Section: Antileprosy Drugs and Drug Resistancementioning
confidence: 99%
“…However, Chang et al (1952) reported a high safety level in the sulphones. Cochrane (1952) suggested that the basis of their proper use is to start with small doses of dapsone and gradually increase them to the maximum dose. The question that arises is: need dapsone be started in low dosage if the patients tolerate the drug well?…”
Section: Introductionmentioning
confidence: 99%